A Comparative Analysis Between Positive Law and Islamic Fiqh on the Phenomenon of Money Politics in ElectionsPublic in Aceh Singkil Regency - Sayuti Sayuti; Nufiar; Yuni Roslaili; Jailani (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Money politics remains a significant challenge to electoral integrity in Aceh Singkil Regency, creating tension between democratic principles, positive legal norms, and the Islamic values embraced by the majority of the population. This study aims to comparatively analyze the perspectives of Indonesian positive law and Islamic jurisprudence on the phenomenon of money politics and to formulate an integrative framework for its eradication within the context of a region implementing Islamic law. This research employed a qualitative library research design with a comparative approach. Data were collected through documentary analysis of election laws and regulations, classical and contemporary fiqh literature, scholarly books, journal articles, and relevant research reports. The findings reveal that positive law defines money politics within a relatively narrow procedural and material framework, emphasizing formal legal elements, criminal sanctions, and strict evidentiary requirements. In contrast, Islamic jurisprudence conceptualizes money politics as risywah, encompassing all forms of benefits intended to influence political decisions, supported by broader moral, social, and spiritual sanctions as well as a more flexible evidentiary approach. The study further demonstrates that each legal system possesses distinct strengths and limitations in addressing electoral bribery. Consequently, an integrated model combining the legal certainty of positive law with the ethical and preventive values of Islamic jurisprudence is necessary. Such integration may be implemented through regulatory harmonization, religious-based political education, community participation, and local social control mechanisms. In conclusion, strengthening synergy between state legal institutions and Islamic moral values offers a more comprehensive strategy for preventing and combating money politics, thereby promoting cleaner, fairer, and more accountable elections in Aceh Singkil Regency.